2020
DOI: 10.1093/cid/ciaa539
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With Clinical Outcomes in 323 Coronavirus Disease 2019 (COVID-19) Hospitalized Patients in Wuhan, China

Abstract: Background With evidence of sustained transmission in more than 190 countries, coronavirus disease 2019 (COVID-19) has been declared a global pandemic. Data are urgently needed about risk factors associated with clinical outcomes. Methods A retrospective review of 323 hospitalized patients with COVID-19 in Wuhan was conducted. Patients were classified into three disease severity groups (non-severe, severe, and critical), base… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
211
7
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(252 citation statements)
references
References 36 publications
18
211
7
3
Order By: Relevance
“…Previous studies found that advanced age and presence of comorbidity (e.g., cardiovascular disease or hypertension) were risk factors associated with an adverse outcome such as admission to intensive care unit (ICU), need for mechanical ventilation, or death (7,8). In addition, some laboratory indicators e.g., elevated hypersensitive troponin I, leukocytosis, neutrophilia, lymphopenia, and elevated D-dimer were found to be linked with unfavorable clinical outcomes (7)(8)(9). Presence of consolidation on computed tomography (CT) was also considered to be predictive of poor outcome in COVID-19 (10).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that advanced age and presence of comorbidity (e.g., cardiovascular disease or hypertension) were risk factors associated with an adverse outcome such as admission to intensive care unit (ICU), need for mechanical ventilation, or death (7,8). In addition, some laboratory indicators e.g., elevated hypersensitive troponin I, leukocytosis, neutrophilia, lymphopenia, and elevated D-dimer were found to be linked with unfavorable clinical outcomes (7)(8)(9). Presence of consolidation on computed tomography (CT) was also considered to be predictive of poor outcome in COVID-19 (10).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in our study, we analyzed the effect and revealed that COVID-19 patients with persistent negative PCR results tended to have disease progression. This might be explained by older age, accompanying hypertension, more severe status upon admission and elevated CRP, NLR, IL-6, D-dimer, or troponin in these patients to some extent, since other studies previously reported effects of these factors on disease progression [32][33][34]. However, after excluding the effect of age, only serum levels of IL-6 and D-dimer were still associated with disease progression, implying that more severe cytokine reactions and microvascular thromboembolism might be the cause of progression in these patients.…”
Section: Discussionmentioning
confidence: 94%
“…Its predictive role is even more relevant considering the low prevalence of obesity in elderly, in our region (9.8% in Piedmont vs. 14.0% in Italy) (22). The real impact of smoking is more debated and less de ned; while some authors advocate its detrimental impact on the patient's prognosis (23), others conversely postulate a protective effect deriving from the down-regulation of Angiotensin Converting Enzyme-2 (ACE-2) expression in lungs (24). According to our data, current smokers are at increased risk of mortality, although we should acknolwedge that this information, as well as details about history of smoking, could not be retrieved for around one-hundred patients, making it challenging to accurately evaluate the effect of this risk factor.…”
Section: Discussionmentioning
confidence: 99%